2020
DOI: 10.1016/j.ijheatmasstransfer.2019.119135
|View full text |Cite
|
Sign up to set email alerts
|

Heat pipe dryout and temperature hysteresis in response to transient heat pulses exceeding the capillary limit

Abstract: The balance between the capillary pressure provided by the wick in a heat pipe or vapor chamber and the flow resistance to liquid resupply at the evaporator determines the maximum heat load that can be sustained at steady state. This maximum heat load is termed as the capillary limit; operation at steady heat loads above the capillary limit will result in dryout at the evaporator wick. However, different user needs and device workloads can lead to highly transient heat loads in applications ranging from consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…The transient response of a flat copper heat pipe subjected to heating power inputs exceeding the capillary limit was studied by Baraya et al [104]. The temperature response of the 150 mm (L) Â 9 mm (W) Â 0.62 mm (H) heat pipe was then examined when a heating power of 10 W, higher than the capillary limit (of 5.1 W), was supplied for 10 s from an initial steady-state heating power of 3 W. Sharp increases in the evaporator and condenser temperatures were seen when the heating power was stepped up.…”
Section: Fixed Conductance Heat Pipes/vapor Chambersmentioning
confidence: 99%
“…The transient response of a flat copper heat pipe subjected to heating power inputs exceeding the capillary limit was studied by Baraya et al [104]. The temperature response of the 150 mm (L) Â 9 mm (W) Â 0.62 mm (H) heat pipe was then examined when a heating power of 10 W, higher than the capillary limit (of 5.1 W), was supplied for 10 s from an initial steady-state heating power of 3 W. Sharp increases in the evaporator and condenser temperatures were seen when the heating power was stepped up.…”
Section: Fixed Conductance Heat Pipes/vapor Chambersmentioning
confidence: 99%
“…Baraya et al studied the transient thermal response of a heat pipe subjected to heat input pulses of varying duration that exceed the capillary limit. It is demonstrated that under such transient heating conditions, a heat pipe can sustain heat loads higher than the steady-state capillary limit for brief periods of time without experiencing dryout [26]. Wang et al experimentally analyzed the heat transfer limit for high L/D potassium heat pipe operating with inclination angle [27].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used active and passive two-phase cooling technologies may not be sufficient for cooling ever-shrinking electronic devices with heat dissipation exceeding 1000 W/cm 2 [1][2][3]. Capillarydriven two-phase systems like heat pipes and vapor chambers achieve high heat transfer coefficients without the need of an external power; however, they are prone to severe challenges related to their capillary limit [4]. Although pumped two-phase technologies like micro/minichannel heat sinks have been demonstrated to remove large heat fluxes while operating with low pumping power, they are prone to flow boiling instabilities that have catastrophic impacts on the thermal performance of the cooling system [5].…”
Section: Introductionmentioning
confidence: 99%